Atomic Ionization by Dark Matter Particles. (July 2015) - Flambaum, V V; Dzuba, V A; Pospelov, M; Derevianko, A; Roberts, B.
Synopsis: Using the relativistic Hartree-Fock approximation, we calculate the rates of atomic ionization by absorption of axions and other Dark matter candidates. We also calculate atomic ionization by scattering of heavy Dark matter particles on electrons. The results are used to interpret possible detection of Dark matter by DAMA collaboration.